1991
DOI: 10.1111/j.1365-246x.1991.tb06725.x
|View full text |Cite
|
Sign up to set email alerts
|

The British Siluro-Devonian palaeofield, the Great Glen Fault and analytical methods in palaeomagnetism: comments on paper by K. M. Storetvedtet al.

Abstract: Late Silurian-early Devonian palaeomagnetic poles throughout the British Isles lie in a coherent group about 1"s and 314"E (Ag5 = 9.6"). The clustering of these poles, which are derived from 11 individual studies of Siluro-Devonian rocks of all the major tectonic elements of Britain, carries two important tectonic implications:(1) the British sector of the Iapetus Ocean, recognizable from Ordovician poles, had closed by late Silurian times; and(2) any postulated mega-shear, whether related to Acadian or Hercyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As the main folding is regarded to be Upper Silurian to Lower Devonian (Dewey 1963), the B magnetization may have been in existence already from late Silurian time. For more than 25 years the Siluro-Devonian palaeomagnetic field relative to the British Isles has been a matter of repeated debate (see Torsvik, Trench & Smethurst 1991;Storetvedt et al 1992 for recent contributions to this discussion). In short.…”
Section: N T E R P R E T a T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main folding is regarded to be Upper Silurian to Lower Devonian (Dewey 1963), the B magnetization may have been in existence already from late Silurian time. For more than 25 years the Siluro-Devonian palaeomagnetic field relative to the British Isles has been a matter of repeated debate (see Torsvik, Trench & Smethurst 1991;Storetvedt et al 1992 for recent contributions to this discussion). In short.…”
Section: N T E R P R E T a T I O Nmentioning
confidence: 99%
“…For more than 25 years the Siluro-Devonian palaeomagnetic field relative to the British Isles has been a matter of repeated debate (see Torsvik, Trench & Smethurst 1991;Storetvedt et al 1992 for recent contributions to this discussion). In short.…”
Section: N T E R P R E T a T I O Nmentioning
confidence: 99%
“…(1990), amongst others. Many of these postulated large-scale displacements have since been disproved, as some of the palaeomagnetic studies upon which they were based have been shown to be inadequate in resolving complex magnetization histories, leading to interpretations based on comparisons of components of different ages (Briden, Turnell & Watts 1984;Irving & Strong 1984, 1985Torsvik, Trench & Smethurst 1991a). We conclude, therefore, that there is no palaeomagnetic evidence for Devonian or late Palaeozoic tectonic discordance between Laurentia and its margins.…”
Section: The Tectonic Integrity O F Laurentja a N D Its Marginsmentioning
confidence: 83%
“…(2) We recognized T as a trajectory on the vertical plot only with no corresponding branch in the horizontal plot (Storetvedt et al 1990, p. 160), and we argued that this is probably the result of partial spectra overlap of two components. With the new information on temperature steps and their sequential order (Torsvik et al 1991 (1989) claim that their high-temperature remanence is pre-tectonic, but the direction arrived at for this sample is anomalously steep even for the intermediately inclined palaeomagnetic axis they adhere to. They further argue that we applied improper analytical procedures in our analyses.…”
mentioning
confidence: 95%
“…With the new information on temperature steps and their sequential order (Torsvik et al 1991, this volume), we consider our original point as well emphasized. A perusal of fig.…”
mentioning
confidence: 99%